Solutions for Trust of Applications on Untrustworthy Systems - Hill, Jonathan; Knight, John; Davidson, Jack (University of Virginia, Department of Computer Science, 2000)
Distributed systems rely on non-local applications. At the same time, non- local applications can only be trusted as far as a non-local systems can be trusted. This is inadequate for the purposes of monitoring and maintaining critical infrastructure that relies on a distributed computer system. We require a distributed, flexible, and reliable application system to act non- locally throughout a network. Flexibility encourages a model that utilizes application level processes, dispatched from a trusted source system to untrustworthy non-local systems in the network. Reliability requires that the local system be aware of the state of operation of its dispatched application on the inherently untrustworthy non-local system. Unfortunately, these requirements lead to a scenario of a trust gap, in which a dispatched application level process must correctly function while relying on non-local (to the dispatcher, local to the application) system services which cannot be trusted. This is the inverse problem of the untrustworthy incoming application, in which a trusted system is asked to support an untrustworthy application. As such, a trust gap comes with a critical, unique, and difficult set of properties of great importance for the development of fault tolerant distributed systems. In this paper we will consider hardware and low-level software solutions to the trust gap problem. We develop a taxonomy of possible solutions and investigate the promise of each approach. Of these, we find two solution approaches with potential and applicability to today's distributed computing environments.
Original submission date: 2012-10-29T19:12:15Z